Bouncing Cosmology in fG,T Gravity with Logarithmic Trace Term - M. Farasat Shamir (Advances in Astronomy)
This study is devoted to explore bouncing cosmology in the context of fG,T theory of gravity. For this purpose, a Gauss–Bonnet cosmological model with logarithmic trace term is considered. In particular, the possibility of obtaining bouncing solutions by considering two equations of state parameters is investigated. A graphical analysis is provided for analyzing the obtained bouncing solutions. The energy conditions are discussed in detail. It is interesting to notice that null and strong energy conditions are violated near the neighborhood of bouncing points justifying the accelerating universe in the light of the recent observational data. The behavior of the scale factor, red shift function, deceleration parameter, and Hubble parameter is also debated. An important feature of the current study is the discussion of conservation equation in fG,T gravity. The possibility of some suitable constraint equations which recover the standard conservation equation is discussed, and all the free parameters are assumed accordingly. All the results in this study suggest that the proposed fG,T gravity model provides good bouncing solutions with the chosen EoS parameters.